1999
DOI: 10.1192/bjp.175.4.357
|View full text |Cite
|
Sign up to set email alerts
|

Altered cerebral perfusion measured by SPECT in relatives of patients with schizophrenia

Abstract: Medication- and symptom-free relatives had altered regional perfusion intermediate between subjects with schizophrenia and controls. Impaired perfusion, verbal memory and P300 appear to be related traits associated with an increased risk of illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(20 citation statements)
references
References 64 publications
2
18
0
Order By: Relevance
“…P300 amplitude reduction may not be specifically related to an increased risk for alcohol dependence as reduction in amplitude has been found in association with other psychiatric disorders. A family study that recorded auditory event-related potentials from members of 20 multiplex families with schizophrenia found P300 latency delayed and amplitude reduced in schizophrenics in comparison to controls and in about half of the asymptomatic relatives, though not all families were characterized by this pattern [Blackwood et al, 1999]. A segregation analysis using ERP characteristics found P300 latency as a marker for predisposition to schizophrenia [Sham et al, 1994].…”
Section: Discussionmentioning
confidence: 99%
“…P300 amplitude reduction may not be specifically related to an increased risk for alcohol dependence as reduction in amplitude has been found in association with other psychiatric disorders. A family study that recorded auditory event-related potentials from members of 20 multiplex families with schizophrenia found P300 latency delayed and amplitude reduced in schizophrenics in comparison to controls and in about half of the asymptomatic relatives, though not all families were characterized by this pattern [Blackwood et al, 1999]. A segregation analysis using ERP characteristics found P300 latency as a marker for predisposition to schizophrenia [Sham et al, 1994].…”
Section: Discussionmentioning
confidence: 99%
“…This is as a result of the welldocumented deficits in particular cognitive tasks involving learning and memory in individuals with schizophrenia, bipolar disorder and unipolar major depression. [60][61][62] Presynaptic changes in kainate receptor-dependent plasticity have been described at hipocampal mossy fibre synapses, 63,64 suggesting that the expected reduction in GRIK4 protein levels in the karyotypically abnormal patient might be expected to modify kainate receptor channel properties, and their contribution to LTP, by altering subunit stoichiometry.…”
Section: Discussionmentioning
confidence: 99%
“…P300 shows reduced amplitude and increased latency in patients with schizophrenia and their relatives (Blackwood et al, 1991;Freedman and Squires-Wheeler, 1994) and also in families of patients with bipolar disorder (Pierson et al, 2000). In patients with schizophrenia, P300 changes correlate with cognitive impairment including verbal memory and verbal fluency deficits (Souza et al, 1995;Shajahan et al, 1997a;Blackwood et al, 1999) and are accompanied by altered regional cerebral blood flow measured by SPECT (Shajahan et al, 1997b). Eye movement abnormalities have been widely studied in schizophrenia (Levy et al, 1994), and Arolt et al (1996) identified a chromosome 6 locus for an eye tracking endophenotype.…”
Section: Intermediate Phenotypes (Endophenotypes)mentioning
confidence: 98%